The Complexity Paper: A Writing Assignment that Targets Cognitive Bias - Southworth, James (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2023)
Cognitive bias, especially confirmation bias and motivated reasoning, poses a significant challenge to argumentative writing genres, including the persuasive essay. To address this challenge, I introduce the complexity paper. Rather than attempting to convince the reader of a particular position on an issue as with a persuasive essay, the goal of a complexity paper is to convince the reader that the issue under discussion is difficult to resolve. This altered motivational structure encourages the writer to engage in perspective taking, thereby addressing confirmation bias and motivated reasoning. I outline a three-part structure of the complexity paper using the example of physician-assisted suicide with the goal to help university instructors implement this genre into their courses. I recommend incorporating a complexity paper into a writing scaffold structure that precedes an argumentative paper.